A Methodology for Organizing Virtual and Remote Laboratories - Zervas, P.; Kalamatianos, A.; Tsourlidaki, E.; Sotiriou, S.; Sampson, Demetrios (2014)
Virtual and remote laboratories provide access to state-of-the-art science experiments and are capable of providing students with innovative learning opportunities. Such environments can be highly effective in increasing students’ interest in science and their engagement in relevant learning activities. In order to increase the findability of available virtual and remote laboratories, we propose their storage and organization into web-based repositories. To this end, this chapter aims: (a) to take stock of the current landscape of available repositories of virtual and remote laboratories and identify common metadata elements, (b) to propose a methodology for organizing virtual and remote laboratories by exploiting common metadata elements from existing repositories and (c) to introduce the concept of big ideas of science for classifying virtual and remote laboratories based on fundamental ideas of the real world.